Analisa Kualitas, Keamanan, Kemudahan, dan Kecepatan dari Sistem Informasi Akuntansi di Perusahaan Global Tiket Network - Saragih, Andrean Wismar Putra; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 31 No 7 (2021), 2021)
On the website www.tiket.com, consumers can make online payments with various methods. This payment method requires a quality accounting information system. All financial activities that use the system will be carried out by the system operator, where the performance of this system operator has an important role in the overall performance of the company. The following research aims to determine the quality, security, ease of use and speed of access to accounting information systems at PT. Global Ticket Network. Population and sample 40 people. The sample method uses the census method. The analysis tool uses a qualitative descriptive technique. Based on the results of the study, AIS Quality, AIS Security, AIS Ease and SIA speed at PT. Global Tiket Network is already good. This is in accordance with the results of the questionnaire to 40 employees as respondents. Keywords: Accounting Information System; Quality.